KRITIK SOSIAL DALAM CERPEN-CERPEN SURAT KABAR HARIAN JAWAPOS EDISI APRIL 2015 DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Abdurrahman, Muhammad Rizki Asrul, Yasnur Asri, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This study aims to: (a) describe social issues that are the focus of author criticism in short stories in the April 2015 Jawapos newspaper. (B) describe the form of social criticism submitted by authors in short stories in Jawapos April 2015. (C) to describe the implications of the Jawapos short story study in the April 2015 edition of Indonesian language learning. The type of this research is qualitative research by using descriptive method of content analysis. The results of this study are social problems contained in the April 2015 edition of Jawapos short stories, namely (1) the problem of poverty (2) the problem of crime (3) the problem of the young generation in modern society (4) religious issues and beliefs (5) Environment (6) family disorganization problem. Furthermore, the form of social criticism submitted by the authors in short stories in Jawapos (April) edition of the Jawapos newspaper, (1) the direct form of criticism (2) the cynical form of criticism (3) the symbolic form of the delivery of criticism (4) the form of humorous criticism 5) the interpretive form of interpretive submission. Further implications for learning Indonesian.Kata kunci: kritik sosial, cerpen, surat kabar jawaposÂ